Analysis of factors associated with IUI pregnancy outcomes in elderly and young patients - Chunmei- Yu; Lijing- Bai; Jian mei-Zhou; Xiao yu-Wang; Li Chen; Jinghua- Zhang (BMC, 2024)
Abstract Objective The objective of this study was to investigate the correlation between various factors and the clinical outcomes of Intrauterine Insemination (IUI) in both young and aged patients, aiming to provide a theoretical basis for clinical consultations. Methods This retrospective analysis examined a total of 4,221 IUI cycles conducted at the Reproductive Center of Changzhou Maternal and Child Health Hospital between January 2016 and December 2020. The patients were categorized into two groups based on age: the elder group (≥ 35 years) and the young group (< 35 years). Results The findings of this study revealed a significant association between woman's age and BMI with pregnancy outcomes (0.93, 95% CI: 0.89-0.97) (1.04, 95% CI: 1.01-1.06). Moreover, in young women, both age and Body Mass Index (BMI)were found to be related to pregnancy outcomes (0.97, 95% CI: 0.89-0.97) (1.08, 95% CI: 1.01-1.06). Additionally, BMI and the number of cycles in aged IUI patients were found to be associated with pregnancy outcomes. The pregnancy rate in the second cycle was approximately 1.9 times higher than that in the first cycle (1.9, 95% CI: 0.97-3.77), and in the third cycle, it was approximately 3 times higher than that in the first cycle (3.04, 95% CI: 1.43-6.42). Conclusions In conclusion, there is an association between woman's age and BMI and the clinical outcomes of IUI. However, the number of cycles did not affect the pregnancy outcomes in young women. Conversely, in elder women, the number of cycles was found to be related to the IUI pregnancy outcomes, with significantly higher pregnancy rates observed in the second and third cycles compared to the first cycle.